Iron Deficiency Anemia in Growing Years and its Effect on Cognition: A Review - Prabhavathi, S.N.; Prakash, Jamuna (International Journal of Child Health and Nutrition, 2014)
Iron deficiency anemia is a widespread nutritional problem. Children are particularly vulnerable due to poor maternal iron status and inadequate diet. Since iron plays a vital role in neurological development, its deficiency in early life can lead to altered cognition and motor development. Severe iron deficiency during infancy can affect the major processes such as myelination, development of neurotransmitter pathways, neural metabolism and neural plasticity. The present review intends to provide information on the various effects of iron deficiency during different stages of life cycle. Clinical trials conducted on both humans and animals have established that infants who suffer iron deficiency during the early years of life are known to be under risk for experiencing the long lasting effect of early iron deficiency in future years also. Follow-up studies conducted on infants showed that the anemic children continued to exhibit lower cognitive development compared to their non-anemic counterparts and also had difficulty in the development of motor control tasks. Hence, there is a need to identify and correct iron deficiency anemia during the early years of life to prevent possible future complications.